Technical Aspects in Heat and Electric Energy Production by Waste Biomass Gasification in South Moravia Sawmill - Tadeáš OCHODEK; Jan NAJSER; Rafał CHŁOND (Transactions of the VŠB-Technical University of Ostrava, Mechanical Series, 2011)
The paper presents results of tests on a pilot plant using waste from the process timber. Experiments presented were obtained from the gasification of different biomass fuels, as well as various types of reactors. Presented biomass gasification technology shows the optimization process of converting fuel to its energy use in cogeneration unit. Installation requires few refinements of various gas purification components and the preparation of a long work to obtain the best possible economic effects.